First taxonomic records of epizoic freshwater algae on golden apple snails (pomacea canaliculata lamarck) from rice paddies in Laguna (Philippines) - Arguelles, Eldrin DLR (Vol. 150, No. 4 (August 2021) pages 829-844.)
"In rice paddies where hard substrate is considered as a limiting resource, the hard shell of mollusks can serve as a primary settling space of algal epibionts. The study presents the first taxonomic survey to report and describe epizoic algae in freshwater snail - golden apple snail (GAS) (Pomacea canaliclata Lamarck) - found in agricultural areas. A total of 17 microalgal taxa belonging to 12 orders, 16 families, and 17 genera were taxonomically identified and described from the collected samples, all of which are considered new distributional records of microalgae in the Philippines"-Title page.